The GTP binding proteins Gem and Rad are negative regulators of the Rho–Rho kinase pathway - Ward, Yvona (The Rockefeller University Press, 2002)
The cytoskeletal changes that alter cellular morphogenesis and motility depend upon a complex interplay among molecules that regulate actin, myosin, and other cytoskeletal components. The Rho family of GTP binding proteins are important upstream mediators of cytoskeletal organization. Gem and Rad are members of another family of small GTP binding proteins (the Rad, Gem, and Kir family) for which biochemical functions have been mostly unknown. Here we show that Gem and Rad interface with the Rho pathway through association with the Rho effectors, Rho kinase (ROK) α and β. Gem binds ROKβ independently of RhoA in the ROKβ coiled-coil region adjacent to the Rho binding domain. Expression of Gem inhibited ROKβ-mediated phosphorylation of myosin light chain and myosin phosphatase, but not LIM kinase, suggesting that Gem acts by modifying the substrate specificity of ROKβ. Gem or Rad expression led to cell flattening and neurite extension in N1E-115 neuroblastoma cells. In interference assays, Gem opposed ROKβ- and Rad opposed ROKα-mediated cell rounding and neurite retraction. Gem did not oppose cell rounding initiated by ROKβ containing a deletion of the Gem binding region, demonstrating that Gem binding to ROKβ is required for the effects observed. In epithelial or fibroblastic cells, Gem or Rad expression resulted in stress fiber and focal adhesion disassembly. In addition, Gem reverted the anchorage-independent growth and invasiveness of Dbl-transformed fibroblasts. These results identify physiological roles for Gem and Rad in cytoskeletal regulation mediated by ROK.